Building a set of criteria for selection of natural clam beds (Lutraria rhynchaena, Jonas 1844) as broodstock source for seed production and gene conservation in Cat Ba - Ha Long bay - Hao, Do Manh; Tuyet, Dao Thi Anh; Dat, Nguyen Tien; Nga, Hoang Thi Thanh; Hiep, Le Minh; Quan, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2019)
Building on a set of criteria used as a scientific basis for conservation zoning of natural marine resources is essential. In this study, we propose the set of criteria to select the suitable natural clam beds of Lutraria rhynchaena for protection priority from 16 sites in Cat Ba - Ha Long bay. Research results have built a set of 13 different criteria, including area, density, benthic substrate, food organisms, turbidity, water flow, water depth, predators, salinity, benthic organisms, pollution, area location and zoning conflicts. The criteria are divided into 5 groups, in which the area and density have the highest coefficent of 5, followed by the zoning conflict with the coefficient of 4, the pollution with the coefficient of 3, the efficient of benthic substrate and water flow is 2, the remaining criteria have a same coefficient of 1. The highest points are evaluated at Tung Sau bed (station 12) with a score of 254 points, followed by Van Boi beach (station 7) with a score of 235 points, the bed is in Trinh Nu Cave (Station 13) with a score of 229 points, which are proposed to be prioritized sites for conservation